Globalization, Tax Competition and Tax Burden İn Turkey - Veli KARGI (International Journal of Public Finance, 2016)
1990’s world was quite different from the world of 1950’s. Especially in the last twenty years, the increasing involvement of Japan in the world economy since the 1990s, in addition to the dominance of globalization and market economy throughout the world, the rapid spread of information resulting from the developments in IT-technology and the international competition emerging in the field of technology have all led to some significant developments in the world economy.